(untitled) (The Pakistan Development Review, 2015)
Zakat is an annual religious levy that is collected from rich Muslims and its proceeds are disbursed among poor people of the society. It has many spiritual and social merits. For example, it purifies the hearts of zakat-givers as they give away a part of their wealth, one of the most precious things in their lives, seeking the pleasure of God without requiring any worldly gains whatsoever. It bridges the social gap between „haves‟ and „have-nots.‟ This study analyses, however, only economic consequences of Zakat for economic growth. They cannot be appreciated duly unless one understands the following concepts of modern economics; various theories of consumption, aggregate demand, stagnation thesis, consumption puzzle, marginal productivity of capital and Kuznets curve.